The Influence of Green Product, Green Marketing, and Brand Image on Consumer Purchasing Decisions of Bottled Water - Ignatius Agus Suryono; Abdurrazak Alfan; Sudaryatie Sudaryatie (Journal of Economics and Business UBS, 2023)
As time progresses, accompanied by the rapid advancement of technology, the awareness and concern of society regarding the importance of preserving the environment has increased. The environmental awareness movement, promoted by both the government and initiatives from society, has begun to be campaigned throughout Indonesia. Business actors as producers who generate various types of waste that have the potential to disrupt environmental sustainability now need to implement the concepts of sustainability and eco-friendliness. Changes in the lifestyle of society, which currently tends to be practical and instant, have resulted in the emergence of various products that support these desires. The bottled water industry in Indonesia has experienced growth and development from year to year. Looking at the various phenomena above, many companies have gradually shifted to using environmentally friendly raw materials for their products. The study was conducted through a survey using a questionnaire as a data collection tool. The population and sample in this study are 128 consumer students from FEB UPN "Veteran" Yogyakarta, using primary data with the purposive sampling method. The criteria for respondents in this study are consumers who are active students of FEB UPN "Veteran" Yogyakarta, considering purchasing bottled water, considering green products when purchasing bottled water products, considering green marketing when purchasing bottled water products, and considering the brand image of bottled water when making a purchase decision. The data analysis technique used is the multiple linear regression technique. The results show that: 1) the Green Product, Green Marketing, and Brand Image together have a significant influence on purchase decisions, 2) the Green Product has a positive and significant influence on purchase decisions, 3) Green Marketing has a positive and significant influence on purchase decisions, 4) Brand Image has a positive and significant influence on purchase decisions.